A cohesive damage-plasticity model for DEM and its application for numerical investigation of soft rock fracture properties. (November 2017) - Nguyen, Nhu H.T.; Bui, Ha H.; Nguyen, Giang D.; Kodikara, Jayantha
Abstract: The failure of soft rocks is highly concerned in both research and practice due to the vulnerability of materials and its involvement in a wide range of foundation and mine collapses. Different methods have been suggested to study the fracture characteristics of soft rocks. In this study, a discrete-based modelling method is proposed, as an alternative to existing continuum methods, to analyse the fracturing behaviour of soft rocks. A new cohesive model coupling damage mechanics with plasticity theory is formulated to characterise the failure mechanisms of cement bridges between aggregates in the materials. In conjunction with the discrete element method (DEM), the proposed modelling method can produce realistic modelling of soft rock failure, demonstrated through good agreements between experimental and numerical results in both specimen responses and crack patterns. Based on this, further analyses of soft rock failure are carried out, focusing on the influence of specimen geometries on the material fracture toughness measured in a semi-circular bending test. The simulation results agree well with their experimental counterparts while being less scattered than the experimental data. This demonstrates the effectiveness of the proposed method in characterising fracture properties of soft rocks and opens more potentials for a better understanding of soft rock failure. Highlights: Failure of soft rocks can be effectively captured using a new cohesive model combined with DEM. The combined damage-plasticity cohesive model can describe well the degradation of cement bridges in soft rocks. This facilitates the characterisation of soft rock failure for better understanding and design.